High Levels of Spatial Heterogeneity in The Biodiversity of Soil Prokaryotes on Signy Island, Antarctica - Chong, C.W.; Pearce, D.A.; Convey, P.; Tan, G.Y.A.; Wong, R.C.S.; Tan, I.K.P. (2010)
In a previous study, soil bacterial diversity at environmentally distinct locations on Signy Island was examined using denaturing gradient gel electrophoresis (DGGE) profiling, and a range of chemical variables in soils was determined in order to describe variations between them. The dominant bacterial communities of all locations were found to be significantly different, although higher levels of similarity were observed between locations with similar physico-chemical characteristics, such as at penguin rookeries, seal wallows and vegetated soils. Extending this study, here soil prokaryote biodiversity was compared between 15 distinct locations in order to elucidate any interaction between four general habitat types on Signy Island (South Orkney Islands, maritime Antarctic) and any influence of previous human impacts at these sites. Specific sites were selected to represent the range of different soil environments present and to cover a range of environmental factors present in the maritime Antarctic which are known to influence bacterial community composition in soils elsewhere. A diverse prokaryote community is described, again with the majority of excised and sequenced bands belonging to the Bacteroidetes. Although DGGE profiling identified significant differences in prokaryotic biodiversity between all sampling sites, aggregations of banding patterns were also apparent across the different soil environments examined. Correlations between specific DGGE profiles and 10 selected soil parameters suggested that much of this variation could be explained by differences in the levels of environmental disturbance and soil pH. In particular, a greater proportion of variation in soil bacterial diversity was explained by differences in soil properties at human-disturbed locations than at undisturbed locations, with higher explanatory values by edaphic factors in the former and soil metal content in the later. In general, our data indicate that small-scale variation is an important factor in understanding patterns of prokaryotic distributions in soil habitats in the maritime Antarctic environment. (c) 2009 Elsevier Ltd. All rights reserved.